Project Based Learning Model in Islamic Education for Enhancing Creativity and Religious Values in Vocational Students - Ahmad Aly Syukron Aziz Al Mubarok; Ahmad Wisnu Saputra (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to analyze the implementation of the Islamic Religious Education (PAI) learning model based on Project-Based Learning (PjBL) in strengthening creativity and religious values ​​of Vocational High School (SMK) students in the context of 21st-century skills (4C). The study was conducted with a qualitative approach and case study design at SMK Angkasa and SMK Awang-awang which have integrated PjBL and 4C competencies in their curriculum policies. Participants consisted of PAI teachers, curriculum managers, and grade XI students who were selected purposively. Data were collected through learning observations, in-depth interviews, and document analysis (RPP, project products, and student reflection journals), then analyzed interactively through the stages of data reduction, data presentation, and drawing conclusions strengthened by triangulation of sources and techniques. The results of the study indicate that PjBL changes the dynamics of PAI learning to be more active, collaborative, and contextual through authentic projects that link the themes of morals and muamalah with the world of workshops. Student creativity is evident in the emergence of original religious ideas and products relevant to the vocational context, while religiosity is strengthened through increased consistency in worship, internalization of the values ​​of trust and honesty, and ethical reflection related to work practices. Theoretically and pedagogically, this study confirms the potential of PjBL as an effective framework for integrating the 4C competencies and fostering religiosity in vocational high schools.